Humanlike robots as employees in the hotel industry: Thematic content analysis of online reviews. Issue 1 (2nd January 2020) - Yu, Chung-En
ABSTRACT: The purpose of this study is to discover the public's general perceptions of robots as frontline employees in the hotel industry based on YouTube online reviews. This study applied data mining techniques to the two most frequently viewed videos related to the employment of robots in hotels. Thematic content analysis was conducted based on the Godspeed dimensions. The findings suggest that potential users' perceptions tend to be negative when it comes to any discussion of humanlike robots. However, people are more receptive towards robots with animated features. Finally, this study contributes to both theoretical and practical discussions on robots and their related modes of analyses. It raises potential problems in the Godspeed scale and uncanny valley theory, provides guidelines to hotels which intend to employ humanlike robots as frontline staff, and offers suggestions, such as promotional videos, to marketers.